Implementation of Digitalization to Enhance Feasibility Testing of Mining Facilities and Equipment Installations - Fathoni*, Naim; Alya, Geafanni Emilla; Nadeak, Ali Amran; Adha, Muhammad Rafly (Riwayat: Educational Journal of History and Humanities, 2023)
Feasibility Testing of Mining Facilities and Equipment Implementation by conducting feasibility tests and maintenance. Mining activities require supporting facilities such as mining facilities, infrastructure, installations, and mining equipment that are declared feasible according to procedures. This involves identifying the needs of facilities, infrastructure, installations, and equipment in accordance with the characteristics of mining activities; determining the list of required facilities, infrastructure, installations, and equipment based on the identification results; developing and establishing procedures for testing the feasibility of facilities, infrastructure, installations, and equipment; conducting feasibility testing of facilities, infrastructure, installations, and equipment; evaluating the results of feasibility testing of facilities, infrastructure, installations, and equipment against the applicable standards; and determining the list of facilities, infrastructure, installations, and equipment declared feasible for operation. The Digitalization of Feasibility Testing for SPIP aims to enhance the feasibility of Facilities (mobile facilities that support mining activities such as Light Vehicles, Buses, Lowboys, etc.), Infrastructure (non-mobile facilities used to support mining activities such as Mess, Workshop, Fuel Station, etc.), Installations (Electrical, Hydraulic, Air, BBC, Water installations, etc.), and Equipment (Heavy Equipment, Lifting Aircraft, Transport, Power Tools, etc.).